Reform of Health Protection Personnel in Armed Criminal Group Areas - Friedrich Max Rumintjap; Ahyar Wahyudi (Formosa Journal of Science and Technology, 2023)
In the context of reforming the protection of health workers in terrorist areas, this conclusion reinforces the fact that protection of health workers is a necessity that cannot be ignored. Health is a human right, and health workers are an important pillar in providing access to the health services needed by communities, including those living in terrorist areas. The threats to health workers in these conflict situations are real and significant. They are at high risk of being targeted by attacks, kidnappings, or other threats, which could hinder much-needed health services for civilians. Strong protection for health workers must be a top priority. This is not only the responsibility of the government, but also the international community and humanitarian organizations. In implementing this reform, measures such as strengthening security in health facilities, better training for health workers in dealing with risky situations, as well as close cooperation with relevant parties are important steps.